Identifications of potential therapeutic targets and drugs in angiotensin II-induced hypertension. Issue 46 (November 2017) - Wu, Xiaoli; Fan, Ruihua
Abstract : Abstract: This study aimed to identify the underlying therapeutic targets of angiotensin II (AngII)-induced hypertension, and screen the related drugs. The gene expression profiles of GSE93579 and GSE75815 were used to identify differentially expressed genes (DEGs) between AngII-induced hypertension and control samples based on meta-analysis. These DEGs were analyzed using Gene-Ontology (GO) function and pathway enrichment methods. Subsequently, the weighed gene coexpression network analysis (WGCNA)-based meta-analysis was applied to determine transcriptional signature with DEGs. Additionally, the functions of the modules were analyzed based on the network, and miRNAs were identified. Finally, small molecule drugs correlation with DEGs was identified. In total, 346 upregulated DEGs (e.g., Rgs7 bp ) and 360 downregulated DEGs (e.g., Ebf3 ) were identified between AngII and control samples. In addition, a total of 150 DEGs in the brown, red, and yellow modules with higher correlation coefficient according to WGCNA, were used to construct the coexpression network, including Rgs7 bp and Ebf3, etc. in brown modules. Besides, 3 modules were obtained after the functions of the modules analysis. Moreover, 5 miRNAs were integrated in modules, including miR-124A, miR-524, miR-493, miR-323, and miR-203. Finally, anisomycin was the highest correlation with DEGs. MiR-124a might be involved in the pathogenesis of hypertension via targeting Ebf3 and Rgs7 bp, which possibly represent a novel and effective strategy for treatment of hypertension. Anisomycin might be performed to reduce blood pressure by blocking MAPK signaling pathway.